CONCEPTUAL FOUNDATIONS AND PROSPECTS FOR EFFECTIVE MANAGEMENT OF REGIONAL BUDGET RESOURCES IN THE DIGITAL ECONOMY (International scientific-electronic journal “Pioneering studies and theories”, 2026)
This study examines the conceptual foundations and prospects for the effective management of regional budget resources in the context of the digital economy. The research analyzes digital transformation processes and ways to improve the efficiency of budget processes through the introduction of e-budget and treasury systems. Scientific recommendations aimed at optimizing regional financial management are proposed.